STUDIES of WATER HYACINTH ( Eichhornia crassipes ) as the BASE of FISHING GEAR MATERIAL - Vanson, Jefri; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted on 15 September to 20 October 2014 Capture Device Materials Laboratoryof Water Resource Utilization Department of the Faculty of Fisheries and Marine Scieces, University of Riau. The method used in this research is the method ofobservation and experimental methods. This study aims to assess the utilization of water hyacinth as a basic ingredient of fishing gear through histological studies, testing water absorption, breaking strength and elongation of the fiber.Based on theresearch of water hyacinth (E. crassipes) with a length of 25 cm, the average value obtained rupture strength was 14.6 kgf, elongation value is equal to 37.4 mm and the average value of water absorption of the sample hyacinth is 2.05103 grams or by 61.923%.Keywords:Naturalfibers, Breakingstrength, Elongation, Water absorption